2003
DOI: 10.1139/w03-061
|View full text |Cite
|
Sign up to set email alerts
|

Identification and use of actinomycetes for enhanced nodulation of soybean co-inoculated with Bradyrhizobium japonicum

Abstract: The utilization of actinomycetes as potential soybean (Glycine max (L.)) co-inoculants was evaluated. Soil samples from Carbondale and Belleville, Ill., were used to inoculate pre-germinated soybean plants to determine antibiotic sensitivity in the native Bradyrhizobium japonicum population. Sensitivity was in the order kanamycin > tetracycline > oxytetracycline > rifampicin > neomycin. Antagonism by five actinomycete cultures toward seven test strains of B. japonicum was also assessed. The ranking average inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
2
21
0
6
Order By: Relevance
“…The first record of antagonistic activity of actinobacteria against rhizobia was reported by Landerkin and Lochhead (1948), which test actinobacteria strains isolated from soil of the genus Rhizobium, and Van Schreven (1964) that compared actinobacteria of the genera Streptomyces, Actinomyces and Nocardia over Rhizobium strains. In Bradyrhizobium japonicum, Gregor et al (2003) observed inhibition of these bacteria in in vitro growth by actinobacteria of the genera Streptomyces and Amycolatopsis. Mingma et al (2014) isolated actinobacteria from roots and rhizosphere of leguminous plants which showed that, strains of the genus Streptomyces have negative effects on the growth of strains of Rhizobium sp.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The first record of antagonistic activity of actinobacteria against rhizobia was reported by Landerkin and Lochhead (1948), which test actinobacteria strains isolated from soil of the genus Rhizobium, and Van Schreven (1964) that compared actinobacteria of the genera Streptomyces, Actinomyces and Nocardia over Rhizobium strains. In Bradyrhizobium japonicum, Gregor et al (2003) observed inhibition of these bacteria in in vitro growth by actinobacteria of the genera Streptomyces and Amycolatopsis. Mingma et al (2014) isolated actinobacteria from roots and rhizosphere of leguminous plants which showed that, strains of the genus Streptomyces have negative effects on the growth of strains of Rhizobium sp.…”
Section: Discussionmentioning
confidence: 98%
“…The antagonistic effect of actinobacteria on the rhizobia was evaluated according to the methods of Gregor et al (2003). The strains of rhizobia were grown in glass tubes with liquid (without agar) YMA medium (10 g of mannitol, 0.5 g of K 2 HPO 4 , 0.2 g of MgSO 4 .7H 2 O, 0.1 g of NaCl, 0.5 g of yeast extract, 5 mL of bromothymol blue, 15 g of agar, 1000 mL of distilled water, and pH 6.8) (Vincent, 1970), and shaken (150 rpm) on a shaker orbital for about seven days.…”
Section: Antagonistic Test In Vitro Between Actinobacteria and Rhizobiamentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were noted by other researchers as well. The combination of Streptomyces kanamyceticus and Bradyrhizobium japonicum increased nodulation and shoot N composition of soybean by up to 55 and 41%, respectively (Gregor et al 2003). Soe and Yamakawa (2013) examined the effect of co-inoculation of Bradyrhizobium yuanmingense MAS34 and Streptomyces griseoflavus P4 in enhancing nodulation, N 2 fixation, and seed yield in different soybean varieties.…”
Section: Pgp Actinobacteria As Helper Bacteriamentioning
confidence: 99%
“…That antibiotics may serve as effectors of signaling systems was clearly demonstrated in studies of the role of actinomycetes in the formation of nodules on the root hairs of leguminous plants [21,22]. Symbiotic rhizobia penetrate the cells of root hairs, causing the formation of nodules, in which nitrogen fixation takes place.…”
Section: Effects Of Calcium Ions On Actinomycete Differentiationmentioning
confidence: 99%